The food price crisis and urban food (in)security - Cohen, Marc J.; Garrett, James (SAGE Publications, 2010)
Both national and international policy responses to the rapid food price increases in 2007 and the first half of 2008 did little to address the very serious impacts on low-income urban dwellers. The speeches, declarations, plans and pledges duly noted the vulnerability of poor urban dwellers to food price rises, as they rely primarily on market purchases for their food (much more so than rural dwellers) and food purchases account for the bulk of their expenditure. Yet most policy prescriptions focused on addressing constraints to rural-based food production. This paper discusses why policy makers should pay greater attention to urban dwellers and describes the multiple pathways through which food price increases have impacts on urban people. It also highlights the evidence on how these impacts have played out during this crisis and discusses how current policy responses could be adjusted and improved to better protect the urban poor in the short and longer term.